2012
DOI: 10.1038/bjc.2012.81
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mutant β-catenin on ABCB1 expression and therapy response in colon cancer cells

Abstract: Background:Colorectal cancers are often chemoresistant toward antitumour drugs that are substrates for ABCB1-mediated multidrug resistance (MDR). Activation of the Wnt/β-catenin pathway is frequently observed in colorectal cancers. This study investigates the impact of activated, gain-of-function β-catenin on the chemoresistant phenotype.Methods:The effect of mutant (mut) β-catenin on ABCB1 expression and promoter activity was examined using HCT116 human colon cancer cells and isogenic sublines harbouring gain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…43,44) In addition, HCT-116 cells express several proteins, including P-gp, MRP, LRP. [45][46][47] Similarly, the expression of ABC transporters including P-gp was detected in B16F10 cells. [48][49][50] Therefore, based on the above information, it can be concluded that in the case of G-II cells, efflux pumps play an active role in mediating their sensitivities to DOX in a drug-concentration dependent manner.…”
Section: Discussionmentioning
confidence: 89%
“…43,44) In addition, HCT-116 cells express several proteins, including P-gp, MRP, LRP. [45][46][47] Similarly, the expression of ABC transporters including P-gp was detected in B16F10 cells. [48][49][50] Therefore, based on the above information, it can be concluded that in the case of G-II cells, efflux pumps play an active role in mediating their sensitivities to DOX in a drug-concentration dependent manner.…”
Section: Discussionmentioning
confidence: 89%
“…For instance, Huang et al demonstrated that the Wnt/β-catenin pathway was involved in the RARγ-induced up-regulation of MDR1 in CRC, and RARγ knockdown would suppress MDR1 expression in CRC cells through the Wnt/β-catenin pathway [31]. Additionally, Stein et al reported that the mutation status of β-catenin could determine the ABCB1 expression in a defined cell line model and in colon cancer specimens [32]. Taken together, we speculate that the main mechanism by which miR-140-5p increases the breast cancer sensitivity to Dox is achieved by reducing the expression of Wnt1/ABCB1 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Both mechanisms can be mediated by the efflux transporters Abcc4 , Abcc5 , and Abcc11 , which are involved in discharging endogenous signaling molecules and nucleoside analogues. It has previously been shown that Wnt/β-catenin directly regulates ABCB1 transporter gene transcription in CML and other malignancies (Corrêa et al, 2012; Stein et al, 2012), and that enforced expression of Irf8 antagonized BCR-ABL and overcame drug resistance (Burchert et al, 2004). It was therefore interesting to see that the leukemic GMP fraction displayed enhanced expression of the ABC superfamily of efflux pumps.…”
Section: Discussionmentioning
confidence: 99%